Logic Programming
DOI: 10.1007/978-3-540-74610-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Logic Programs with Abstract Constraint Atoms: The Role of Computations

Abstract: Abstract. We provide new perspectives on the semantics of logic programs with constraints. To this end we introduce several notions of computation and propose to use the results of computations as answer sets of programs with constraints. We discuss the rationale behind different classes of computations and study the relationships among them and among the corresponding concepts of answer sets. The proposed semantics generalize the answer set semantics for programs with monotone, convex and/or arbitrary constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 18 publications
0
67
0
Order By: Relevance
“…However, it was recently observed that for general logic programs, the FLP answer set semantics may produce answer sets with circular justifications that are caused by self-supporting loops [58,45]. The following two examples well illustrate this behavior.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, it was recently observed that for general logic programs, the FLP answer set semantics may produce answer sets with circular justifications that are caused by self-supporting loops [58,45]. The following two examples well illustrate this behavior.…”
Section: Introductionmentioning
confidence: 85%
“…Shen and You [57] gave an alternative characterization of the conditional satisfaction-based semantics in terms of a generalized Gelfond-Lifschitz transformation. Liu et al [45] proposed a computation-based answer set semantics for normal logic programs with c-atoms, which proves to coincide with the conditional satisfaction-based semantics.…”
Section: Related Workmentioning
confidence: 93%
“…ASPeRiX [12] has been concurrently and independently developed. Both GASP and ASPeRiX have their theoretical roots in the same notion of computation-based characterization of answer sets [16]. ASPeRiX is implemented in C++ and develops heuristics aimed at enhancing the choice of the rules when more of them are applicable.…”
Section: Related Workmentioning
confidence: 99%
“…The work described in [16] provides a computation-based characterization of answer sets for programs with abstract constraints. One of the outcomes of that research is the development of a computationbased view of answer sets for logic programs.…”
Section: Computations and Answer Setsmentioning
confidence: 99%
See 1 more Smart Citation